Adaptation of in vitro turanga-poplar plants to greenhouse conditions - Mikhailenko, N.V.; Turdiyev, T.T.; Kentbaeva, B.A.; Tuigunov, Z.Т.; Kushnarenko, S.V. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The reproduction of turangа-poplar is better carried out by the method of icropropagation, which allows you to obtain high-quality material that is advisable to use in reforestation and landscaping of cities, especially with arid climates. Adaptation of in vitroplants was carried out in greenhouse conditions in containers with a volume of 450 ml. Different in terms of composition substrates were used. The substrate of option 3 turned out to be the most effective: peat and perlite in layers, peat in the lower part, perlite in the upper part; and option 4 — a mixture of peat and black soil in a ratio of 6/4 with a recess filled with perlite. The experiments were carried out in natural daylight in a frame heated greenhouse with a film coating at a temperature of +20...+27 °C. Plants were used in three stages of root system development. After transplantation, they were watered with an antifungal drug solution and water. To prevent evaporation of moisture from in vitro plants and from the surface of the substrate, a transparent cap with a screw-off lid was covered from above. Containers with turangа plants fully adapted to non-sterile conditions were transferred to open areas outside the greenhouse for hardening
Keywords: substrate; drug; non-sterile conditions; plant; invitro; micropropagation; turanga; adaptation